A consumer centred investigation of differentially private risk assessment models in consumer credit - Pena, Ana Rita (2025)
Differential Privacy (DP) is a technology which allows one to gather aggregate information without compromising individual privacy. Over the last few years, it has become the state-of-the-art privacy-enhancing technology. DP has been implemented by several Big Tech companies, as well as governmental bodies, but research in applied contexts is still at a very early stage. As differential private algorithms have an inherent accuracy-privacy trade-off and no guarantees of an equal accuracy loss for different dataset subgroups, when applied in practical settings the accuracy drop could have significant impacts to consumers.